Recent Advancements in Management of Uveitis - Julian, Karina (Pakistan Journal of Ophthalmology, 2018)
Uveitis is a sort of “umbrella term” that encompasses many different diseases, with different etiologies, treatment and prognosis. However, there is a common denominator among them: the potential, more or less important, to produce severe and permanent deficit in visual acuity and/or visual function.1 This concept should be kept in mind whenever we face a patient with uveitis and need to establish the treatment modality. This patient will be most of times young and in working age. Disease’s impact on his life and his social circle should not be underestimated, nor the impact of uveitis as a cause of morbidity and socio-economic blindness within the society.2